Technology Transfer-Based Capacity Building for Organic Fertilizer Production Using Non-Symbiotic Microbial Consortium - Agus Muji Santoso; Siti Zubaidah; Risky Aswi Ramadhani; Hesti Istiqlaliyah; Poppy Rahmatika Primandiri; Tutut Indah Sulistiyowati; Ricko Bintang Ramadhan; M. Raffi Fahriza; Mohamad Wahyu Erwin Santoso; A'a Imam Majid; M. Lani Ira Irawan; Anggi Tias Pratama; Astri Rino Okvitasari; Nurul Bahiyah Binti Abd Wahid (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance partners’ skills in producing solid organic fertilizer using non-symbiotic microbial consortiums and shredding machines through a participatory-collaborative empowerment approach based on the ODSIMED stages. The program was implemented from August to December 2025 with KUB Surya Agrotani in Kediri Regency. Skill data were collected from 56 respondents using structured observation sheets administered at the beginning and end of the mentoring program, while service quality was evaluated through a Likert-scale questionnaire. Descriptive analysis revealed a significant improvement across 10 production skill indicators, with an average N-Gain in the high category (0.89). An important finding was that participants’ compliance with occupational health and safety standards during the mentoring process also increased substantially, with a high N-Gain score (0.84). This result is consistent with the service quality assessment, which indicated that the team of lecturers and students paid strong attention to occupational health and safety standards throughout program implementation. These findings demonstrate that the integration of biotechnology and appropriate technology within the ODSIMED framework effectively strengthens partners’ organic fertilizer production capacity in a measurable and sustainable manner, while maintaining strong attention to health and safety standards.